Penerapan Strategi Pemasaran untuk Meningkatkan Penjualan Mobil Bekas di Heaven Motor - Natalia Sri Endah Kurniawati; Rai Gina Artaningrum (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: The aim of this research is to analyze the marketing strategies that have been implemented at Heaven Motor Company and which strategies can provide the highest sales contribution. Research methodology: This research was conducted at the Heaven Motor Showroom on Jalan Cokroaminoto 327b, Denpasar, Bali. This study is a descriptive study with a qualitative approach. Data were obtained through interviews, observations, and documentation. The analysis process in this research was divided into three stages: data reduction, data presentation, and drawing conclusions. Results: Heaven Motor chose the right strategy to market the cars they sell. The management of customer base data has a very high potential to obtain new customers. Limitations: Sales are limited to units in which the number of sales is not calculated from the amount of money obtained from total unit sales. This research focuses only on marketing strategy and does not include other factors, such as marketing mix, as a factor that influences sales. Contribution: This study contributes to showrooms that have not implemented online marketing strategies, especially following up on customers who have already come to the showroom.